Penggunaan Materi Patristik Joseph Bingham sebagai Pendukung Praktik Pembaptisan Bayi Anglikan - Thianto, Yudha (STT Reformed Injili Internasional, 2022)
Joseph Bingham (1668−1723) was one of the defenders of Reformed Orthodoxy in the Church of England. In his time, he was known as a patristic scholar whose magnum opus, titled Origines Ecclesiasticae, or The Antiquities of the Christian Church, stood as a testimony of his superb studies. This massive work of ten volumes was published between 1708 and 1722. Entangled in a Trinitarian controversy at Oxford University in his younger years, he spent the rest of his life proofing his orthodoxy through his patristic studies and publication. This article focuses on Bingham’s use of the writings of the church fathers in his defense of the theological beliefs and practices of infant baptism in the Church of England. By defending the orthodoxy of the Church of England—by way of its alignment with the church fathers—he indirectly positioned himself in the same line of orthodoxy and therefore purging himself of the tarnished reputation during the height of the Trinitarian controversy at Oxford.